1905 Utah Laws 60, ch. 52, §§ 1-2. - (:unkn) unknown (My University, 1905)
§ 1. Selling or giving firearms to minors under fourteen. Any person who sells, gives or disposes of, or offers to sell, give or dispose of any pistol, gun, target gun, or other firearm, to any person under the age of fourteen years, is guilty of a misdemeanor. § 2. Minor under fourteen must not carry firearms. Any person under the ager of fourteen years who shall carry, or have in his possession, any pistol, gun, target gun or other firearm, unless accompanied by a parent or guardian, shall be guilty of a misdemeanor.
Keywords: CARRY; TRANSFER - MINORS